L’ubérisation des activités productives : un nouveau défi pour les politiques publiques d’aménagement - Adeline Heitz (Netcom)
This article aims to investigate the spatial consequences of the uberization of productive activities. It focuses on two specific sectors, construction and delivery industry, which belong to the productive sector. These activities are particularly affected by the phenomenon of uberization, characterized by the development of digital platforms and the increasing number of self-employed workers in these sectors. The analysis of the location at the regional scale (Ile-de-France) and at the urban scale (EPT Plaine Commune) of self-employed workers in the delivery and construction industries provides insights into 1) the uberization of low-income territories; 2) the residentialization of productive functions. The latter goes against more traditional practices of planning productive activities, which favor economic activity zones.